(untitled) (Web of Teachers: Inderscience Research, 2026)
Career orientation and development, that is, career formation, is attracting attention as one of the priority topics in modern society. It is very important to form career concepts from school days so that young people can find their place in life and become successful and happy people in the future. In a world that is changing every day, with new professions, industries, and activities emerging, students’ knowledge and skills in choosing a career, developing personal qualities, and determining a life path play an important role in their future.